Application of antimicrobial drugs in perioperative surgical incision - Xu Yang; Xurao Xiao; Lefeng Wang; Yue Ao; Yapeng Song; Huabing Wang; Huanan Wang (Annals of Clinical Microbiology and Antimicrobials, 2018)
Abstract Infection in surgical incision often results in poor wound healing, and one of the main factors for wound infection is the use of antimicrobial agents. Rational use of antibiotics is one of the key factors to prevent incision infection in general surgery. The number of current clinical studies on antibiotic use before and during surgery is greater than that of systematic studies on antibiotic use after surgery. For the rational use of antibiotics and improvement of wound healing rate, researchers around the world have gradually focused on the use of antibiotics after surgery. Despite the familiarity on the concept of “rational use of antibiotics”, few clear and systematic studies were conducted to elucidate the effect of different antibiotics on wound healing. Therefore, this review focuses on the use of different types of antimicrobial agents in surgical wounds.